Synthesis and Characterization of Iron(III) Complex Derived from Benzilmonoxime - Soleimani, Esmaiel; Mitu, Liviu (Asian Journal of Chemistry, 2010)
The reaction between benzilmonoxime and iron(III)acetylacetonate in presence of potassium acetate in methanol yielded an orange precipitate. The electronic spectral data for this compound in DMF is in agreement with the octahedral coordination of iron(III). The IR data show that, bidentate ligand benzilmonoximate is bound to iron(III) through the oxygen atom of the carbonyl group and the nitrogen atom of the oxime group. The structure of the complex was determined by X-ray diffraction, cofirmed with an octahedral facial configuration.